Holocene chloroplast genetic variation of shrubs (Alnus alnobetula, Betula nana, Salix sp.) at the siberian tundra-taiga ecotone inferred from modern chloroplast genome assembly and sedimentary ancient DNA analyses - Meucci, Stefano (PhD); Schulte, Luise (Dr.); Zimmermann, Heike H.; Stoof-Leichsenring, Kathleen R. (Dr.); Epp, Laura; Bronken Eidesen, Pernille; Herzschuh, Ulrike (Prof. Dr.) (Ecology and Evolution, 2021)
Climate warming alters plant composition and population dynamics of arctic ecosystems. In particular, an increase in relative abundance and cover of deciduous shrub species (shrubification) has been recorded. We inferred genetic variation of common shrub species (Alnus alnobetula, Betula nana, Salix sp.) through time. Chloroplast genomes were assembled from modern plants (n = 15) from the Siberian forest-tundra ecotone. Sedimentary ancient DNA (sedaDNA; n = 4) was retrieved from a lake on the southern Taymyr Peninsula and analyzed by metagenomics shotgun sequencing and a hybridization capture approach. For A. alnobetula, analyses of modern DNA showed low intraspecies genetic variability and a clear geographical structure in haplotype distribution. In contrast, B. nana showed high intraspecies genetic diversity and weak geographical structure. Analyses of sedaDNA revealed a decreasing relative abundance of Alnus since 5,400 cal yr BP, whereas Betula and Salix increased. A comparison between genetic variations identified in modern DNA and sedaDNA showed that Alnus variants were maintained over the last 6,700 years in the Taymyr region. In accordance with modern individuals, the variants retrieved from Betula and Salix sedaDNA showed higher genetic diversity. The success of the hybridization capture in retrieving diverged sequences demonstrates the high potential for future studies of plant biodiversity as well as specific genetic variation on ancient DNA from lake sediments. Overall, our results suggest that shrubification has species-specific trajectories. The low genetic diversity in A. alnobetula suggests a local population recruitment and growth response of the already present communities, whereas the higher genetic variability and lack of geographical structure in B. nana may indicate a recruitment from different populations due to more efficient seed dispersal, increasing the genetic connectivity over long distances.